The effect of surface wettability on flow boiling characteristics within microchannels. (June 2021) - Vontas, Konstantinos; Andredaki, Manolia; Georgoulas, Anastasios; Miché, Nicolas; Marengo, Marco
Highlights: The effect of surface wettability on flow boiling within microchannels is studied numerically Hydrophilic and hydrophobic surfaces of various contact angle hysteresis at different heat and mass fluxes, are examined Slug flow regime is observed for the majority of the examined cases Liquid film evaporation is the main heat transfer mechanism for the hydrophilic surfaces and contact line evaporation for the hydrophobic Surface wettability can play a significant role on the local and global heat transfer characteristics within microchannels Abstract: The process of flow boiling within micro-passages plays a very important role in many industrial applications. However, there is still a lack of understanding of the effect of an important controlling parameter: surface wettability. In this paper, an advanced numerical investigation on the effect of wettability characteristics on single and multiple bubble growth during saturated flow boiling conditions within a microchannel is performed. The 3D numerical simulations are conducted with the open-source Computational Fluid Dynamics (CFD) toolbox OpenFOAM, utilising a custom user-enhanced Volume Of Fluid (VOF) solver. The proposed solver enhancements involve an appropriate treatment for spurious velocities dampening, an improved dynamic contact angle treatment, as well as the implementation of a phase-change model in the fluid domain also accounting for Conjugate Heat Transfer (CHT) with the solid domain. In total, three sets of simulations of hydrophilic and hydrophobic surfaces with constant heat and mass flux were performed. In the first set, a single bubble seed was patched close to the inlet of the microchannel and the Heat Transfer Coefficient (HTC) along the channel interface was measured until the nose of the bubble reaches the outlet. The bubble growth and transport process within the channel were analysed, with a minor effect of the wettability characteristics on the HTC observed. In the second set of simulations, multiple recurring nucleation events at the same position were simulated; observing that in such more realistic cases the effect of wettability in the HTC was more profound. Finally, simulations with multiple nucleation sites and recurring nucleation events were conducted to analyse cases closer to reality. These results show indeed that surface wettability plays a significant role on the HTC, with the hydrophilic and hydrophobic cases performing approximately 43.9% and 17.8% higher respectively, compared to the single-phase reference simulations. Additionally, it is found that the dominant heat transfer mechanisms for the hydrophilic and hydrophobic surface are liquid film evaporation and contact line evaporation, respectively, and that for the proposed simulation parameters liquid film evaporation can be considered as a more efficient heat transfer mechanism compared to contact line evaporation.